An Extension of RE-AIM to Enhance Sustainability: Addressing Dynamic Context and Promoting Health Equity Over Time - Shelton, Rachel C.; Chambers, David A.; Glasgow, Russell E. (Frontiers in Public Health, 2020)
RE-AIM is a widely adopted, robust implementation science (IS) framework used to inform intervention and implementation design, planning, and evaluation, as well as to address short-term maintenance. In recent years, there has been growing focus on the longer-term sustainability of evidence-based programs, policies and practices (EBIs). In particular, investigators have conceptualized sustainability as the continued health impact and delivery of EBIs over a longer period of time (e.g., years after initial implementation) and incorporated the complex and evolving nature of context. We propose a reconsideration of RE-AIM to integrate recent conceptualizations of sustainability with a focus on addressing dynamic context and promoting health equity. In this Perspective, we present an expansion of the RE-AIM framework to guide planning, measurement/evaluation, and adaptations focused on enhancing sustainability. We recommend consideration of: 1) extension of ‘maintenance’ within RE-AIM to include recent conceptualizations of dynamic, longer-term intervention sustainability and ‘evolvability’ across the life cycle of EBIs, including adaptation and potential de-implementation in light of changing and evolving evidence, contexts, and population needs; 2) iterative application of RE-AIM assessments to guide adaptations and enhance long-term sustainability; 3) explicit consideration of equity and cost as fundamental, driving forces that need to be addressed across RE-AIM dimensions to enhance sustainability; and 4) use or integration of RE-AIM with other existing frameworks that address key contextual factors and examine multi-level determinants of sustainability. Finally, we provide testable hypotheses and detailed research questions to inform future research in these areas.